2021
DOI: 10.1002/tal.1847
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study of unbonded post‐tensioned precast concrete connections with controllable post‐decompression stiffness

Abstract: Summary A new unbonded post‐tensioned precast concrete (PTPC) frame with controllable post‐decompression stiffness (CPDS), achieved by employing novel variable friction energy dissipaters (VFEDs), is proposed in this paper. A steel corbel (SC) is used in the CPDS‐PTPC connection to enhance the shear capacity. The VFED incorporates grooved steel plates and a combination of Bellville washers to provide variable energy dissipation and load‐resisting capacity to achieve target structural performance at different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The second stiffness of the SCPC frame is one of the most important factors that influence the seismic performance of structures after the gap-opening of the connections. According to Huang et al [35], the second stiffness of connections can be changed through two methods: (1) changing the number (stiffness) of prestressed strands or (2) changing the distance of the prestressed strands to the center of the beam section. Therefore, the number of prestressed strands and the distance of the prestressed strands to the center of the beam section were changed to analyze the seismic responses of the structures.…”
Section: The Influence Of Prestressed Strands On the Seismic Performa...mentioning
confidence: 99%
See 1 more Smart Citation
“…The second stiffness of the SCPC frame is one of the most important factors that influence the seismic performance of structures after the gap-opening of the connections. According to Huang et al [35], the second stiffness of connections can be changed through two methods: (1) changing the number (stiffness) of prestressed strands or (2) changing the distance of the prestressed strands to the center of the beam section. Therefore, the number of prestressed strands and the distance of the prestressed strands to the center of the beam section were changed to analyze the seismic responses of the structures.…”
Section: The Influence Of Prestressed Strands On the Seismic Performa...mentioning
confidence: 99%
“…Rodgers et al [33] and Kam and Pampanin [34] proposed that a reduction in stiffness and insufficient energy-dissipating capacity may stimulate the participation of higher modes, causing weak story damage and increasing the local displacement of structures. To enhance the structural stiffness after the decompression of beam-to-column connections, certain authors have proposed a variable friction-damped (VFD) SCPC connection [35] in which the slope friction configuration is used to provide greater stiffness and a higher energy-dissipating capacity when the structure experiences significant displacements. Differing from the hysteresis behavior of common SCPC frames, the VFD-SCPC connection presents three stages of stiffnesses and two instances of activation for dampers, as shown in Figure 1a.…”
Section: Introductionmentioning
confidence: 99%
“…Combining an experimental study with numerical simulation is a common method of identifying the mechanical characteristics of a structural component. [19][20][21][22] A numerical simulation is a robust tool for predicting the nonlinear behavior of a structure. [23] A numerical study also was conducted by ABAQUS/CAE 6.14-2 to generalize the study results for the saddle connection.…”
Section: Numerical Studymentioning
confidence: 99%
“…Reinforced concrete (RC) frame structures, as a structural system that enables flexible space separation, are widely used in Chinese cities. Previous earthquake damage surveys have shown that reinforced concrete frame structures are often severely damaged or even collapse during earthquakes [1][2][3][4]. Therefore, accurate and solid seismic fragility analysis of RC frame structures is important and necessary.…”
Section: Introductionmentioning
confidence: 99%